(untitled) (Research, Society and Development, 2021)
The expansion of the COVID-19 pandemic in Brazil has further evidenced the discrepancy between different social realities of the country, and it may have also impacted eating practices, including those of adolescents. Objective: To evaluate the eating practices of Brazilian adolescents according to socioeconomic status, during the period of social isolation. Method: In this cross-sectional study, demographic, dietary and socioeconomic data were collected from 676 adolescents from all regions of Brazil through an online questionnaire. Associations between social strata and food pattern, food frequency, and changes in food consumption were analyzed by univariate and multivariable logistic regression models. Results: During the COVID-19 pandemic, adolescents in the upper-middle class were more likely to consume milk (p < 0.001), vegetables (p = 0.004), fruits (p < 0.001), and sweets. In contrast, adolescents from the working-lower classes were 53% less likely to eat regular lunch (OR = 0.47, p < 0.001) and 50% more likely to replace large meals by snacks (OR = 1.50, p = 0.03). When assessing the change in food consumption in this period, adolescents from the lower-lower classes were 1.5 to 2 times more likely to increase consumption of sugary drinks (OR:1.71; p = 0.003), fried snacks (OR:1.73, p = 0.005), and ultra-processed foods (OR:1.54, p = 0.02) in comparison with the other social classes. Conclusion: These results suggest a higher risk of unhealthy food consumption among adolescents from lower social classes and can be used as a basis for policies to address the pandemic.